1992
DOI: 10.1159/000261468
|View full text |Cite
|
Sign up to set email alerts
|

Noncariogenicity of Erythritol as a Substrate

Abstract: Erythritol is a sugar alcohol produced by Aureobasidium sp. from glucose. It is 75–80% as sweet as sucrose and is also nonhygroscopic. The aim of this study was to evaluate this sugar substitute from a cariological point of view. Erythritol was neither utilized as a substrate for the lactic acid production nor for plaque formation of mutans streptococci (serotypes a-h) and certain oral microorganisms. It was not utilized for water-insoluble glucan synthesis or cellular adherence by glucosyltransferase from Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 10 publications
1
50
0
2
Order By: Relevance
“…Therefore, it does not provide an energy source (the energy value is 0kcal/g), nor does it cause diarrhoea. Erythritol can be classified as a non-cariogenic sweetener, only one study has reported its cariogenicity 55 . In that study, S.mutans PS-14 and S.sobrinus 6715 did not attach to glass in the presence of erythritol, indicating that erythritol does not appear to be used by mutans streptococci for the synthesis of water-insoluble glucans.…”
Section: Sugar Alcohol (Polyol)mentioning
confidence: 99%
“…Therefore, it does not provide an energy source (the energy value is 0kcal/g), nor does it cause diarrhoea. Erythritol can be classified as a non-cariogenic sweetener, only one study has reported its cariogenicity 55 . In that study, S.mutans PS-14 and S.sobrinus 6715 did not attach to glass in the presence of erythritol, indicating that erythritol does not appear to be used by mutans streptococci for the synthesis of water-insoluble glucans.…”
Section: Sugar Alcohol (Polyol)mentioning
confidence: 99%
“…In vitro incubation with a range of Streptococci species has shown that neither lactic acid [11] nor other organic acids are produced from erythritol. Under the same test conditions, xylitol gave a similar response, whereas maltitol, sorbitol, mannitol, lactitol, and isomalt showed minor acid production.…”
Section: Noncariogenicity Of Erythritolmentioning
confidence: 99%
“…Erythritol is only minimally fermented in the oral cavity by Streptococcus mutans (Kanwanabe et al, 1992) and not fermented in the colon (Arrigoni et al, 2005). As a result, erythritol has an estimated energy value of 0 kcal/g (de Cock and Bechert, 2002;Arrigoni et al, 2005), compared to 4 kcal/g for sucrose (Paul and Southgate, 1978).…”
Section: Introductionmentioning
confidence: 99%